2002
DOI: 10.3133/wri024149
|View full text |Cite
|
Sign up to set email alerts
|

Sources of sodium and chloride in the Scituate Reservoir drainage basin, Rhode Island

Abstract: • Deicing of State and local roads was the largest source of sodium and chloride in the Scituate Reservoir drainage basin during Water Year (WY) 2000. Of approximately 1,000 tons of sodium and 2,300 tons of chloride introduced into the basin, 67 percent of the sodium and more than 90 percent of the chloride came from deicing of State highways, local roads, and other surfaces. Precipitation, individual sewage-disposal systems, and geologic weathering accounted for the remaining 33 percent of the sodium and 10 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The highest annual mean 3 concentrations of chloride and sodium were estimated to be 59 and 35 mg/L, respectively, at the Moswansicut Reservoir (table 6). The relatively high annual mean concentrations of chloride and sodium at Bear Tree Brook (01115275; PWSB station 9; 48 and 28 mg/L, respectively) are the result of residual chloride and sodium leaching to groundwater from a formerly uncovered salt storage pile (Nimiroski and Waldron, 2002) and comparatively small surface-water flows. Annual mean concentrations of chloride and sodium, ranging from 32 to 52 mg/L and 20 to 30 mg/L, respectively, estimated at the unnamed tributary to the Regulating Reservoir (unnamed brook A; 01115120; PWSB station 18) and Peeptoad Brook also were relatively high (table 6).…”
Section: Chloride and Sodium Loads And Yields Estimated From Specific-conductance Monitoring Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The highest annual mean 3 concentrations of chloride and sodium were estimated to be 59 and 35 mg/L, respectively, at the Moswansicut Reservoir (table 6). The relatively high annual mean concentrations of chloride and sodium at Bear Tree Brook (01115275; PWSB station 9; 48 and 28 mg/L, respectively) are the result of residual chloride and sodium leaching to groundwater from a formerly uncovered salt storage pile (Nimiroski and Waldron, 2002) and comparatively small surface-water flows. Annual mean concentrations of chloride and sodium, ranging from 32 to 52 mg/L and 20 to 30 mg/L, respectively, estimated at the unnamed tributary to the Regulating Reservoir (unnamed brook A; 01115120; PWSB station 18) and Peeptoad Brook also were relatively high (table 6).…”
Section: Chloride and Sodium Loads And Yields Estimated From Specific-conductance Monitoring Datamentioning
confidence: 99%
“…The USGS also has been continuously measuring specific conductance at 14 monitoring stations since 2009 (table 1). Equations that relate specific conductance to concentrations of chloride and sodium in stream water were developed as part of previous cooperative studies of the USGS and the PWSB (Nimiroski and Waldron, 2002;Smith, 2015bSmith, , 2018aSmith, , 2021a. These equations, used together with measured (or estimated) streamflows, allow for nearly continuous estimation of chloride and sodium loads to the reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…1). Nimiroski and Waldron (2002) indicated that tributaries in basins with State-maintained roads had substantially higher concentrations of chloride and sodium than tributaries in basins with low road density, presumably because of deicing activities. In addition, sodium is a constituent of potential concern for human health; some persons on restricted diets might need to limit intake of sodium.…”
Section: Chloride and Sodium Loads And Yields Estimated From Specificmentioning
confidence: 99%
“…The highest annual mean 4 concentrations of chloride and sodium were estimated to be 60 and 35 mg/L, respectively, at the Moswansicut Reservoir (table 6). The relatively high annual mean concentrations of chloride and sodium at Bear Tree Brook (53 and 31 mg/L, respectively) are the result of residual chloride and sodium leaching to groundwater from a formerly uncovered salt storage pile (Nimiroski and Waldron, 2002) and comparatively small surface-water flows. Annual mean concentrations of chloride and sodium, ranging from 43 to 52 mg/L and 25 to 30 mg/L, respectively, estimated at the unnamed tributary to the Regulating Reservoir (PWSB station 18), Rush Brook, and Peeptoad Brook (PWSB station 16) also were relatively high (table 6).…”
Section: Chloride and Sodium Loads And Yields Estimated From Specificmentioning
confidence: 99%
See 1 more Smart Citation